Examining the impact of factors on sustainable tourism practices: an empirical study in the Indian context - Swati Naik; Ruby S. Chanda (Cogent Social Sciences)
India’s diverse culture and scenic spots attract tourists from all over the world. Tourist arrivals, both domestic and international, have significantly increased in the country. However, the increase in tourism also gives rise to environmental issues. Hence, the focus of the study is on the behavior of tourists. This article aims to develop and empirically test a conceptual model on the sustainable behavior of tourists. The model included environmental awareness, environmental concern, and perception of negative impacts of tourism as independent variables. SEM analysis was conducted to test the conceptual model. A total of 265 responses were collected from the tourists. The results revealed that environmental awareness and environmental concern have a significant positive influence on the intentions of tourists to follow sustainable practices. While perception of the negative impacts of tourism did not prove to have a significant relationship with intention. There also exists positive significance with the intention to follow sustainable practices and sustainable behavior of tourists. The research article also provides detailed theoretical contributions, practical implications, and gaps for future research studies.